Investigation of teaching the integrated topics on drug abuse in secondary school curriculum - Kimiti, Richard; Mulwa, David M.; Waweru, Samuel N.; Nalelia, Stephen; Muindi, Mathew (My University, 2011)
The problem of this study was to investigate the teaching of the integrated topics on drug abuse in the secondary school curriculum as a strategy to wipe out the problem of drug abuse among students in Machakos District, Kenya. The specific objectives of the study were to: establish the prevalence of drug abuse at the secondary school level according to gender, locality (urban/rural), boarding or day and religious practice, and establish the effect of teaching integrated topics on prevalence rate of drug abuse. It was also meant to examine which topics on drug abuse are integrated in the secondary school curriculum. A survey study was carried out in Machakos District, Kenya. The subjects of the study were drawn from 24 randomly selected secondary schools. A sample of 774 respondents selected through stratified and simple random sampling techniques were used for the study. The sampling matrix comprised of 24 principals, 280 teachers and 470 students. The study utilized five research instruments: three questionnaires, interview schedule and observation schedule. The data collected was analyzed using frequencies, percentages, mean, mode and median. The main findings of the study were: the prevalence of drug abuse according to gender was Boys’ (11.19%), Girls’ (9.58%) and mixed sex (9.49%) schools. The urban schools had a prevalence of 10.73% whereas it was 9.66% in the rural ones. The prevalence according to status of the schools was: Day (13.84%), Mixed Day and Boarding (12.28%), and Boarding (11.54%). The teaching of the integrated topics on drug abuse had helped schools to reduce the drug menace. The topics on drug abuse were integrated in five subjects in the formal curriculum (English, Kiswahili, Chemistry, Biology and Christian Religious Education), the integrated topics were also taught through the non formal (Clubs and societies meetings) and in the informal (class, assembly and dormitory meetings) curriculum.
Keywords: Curriculum; Integrated topics; Prevalence rate of drug abuse